Correlation of safety behavior, handover quality, and risk perception: A cross-sectional study among Chinese psychiatric nurses - Liu, Yakun; Teng, Weiyu; Chen, Chen; Zou, Guiyuan (Frontiers in Psychiatry, 2022)
【Abstract】Background: Nurses’ safety behavior played an important role in patients safety goal realization and nurses’ Safety behavior varies from person to person. However, few research explored the safety behavior level of psychiatric nurses and its influencing factors.Thus,the present research aimed to assess the level of safety behavior, explore whether risk perception mediated the relationship between handover quality and safety behavior among psychiatric nurses. Methods: Through the convenience sampling method, 186 registered psychiatric nurses in a Chinese hospital participated in this cross-sectional study. A total of 186 registered psychiatric nurses were recruited in a Chinese hospital. Handover quality, risk perception and safety behavior were measured. Hayes' PROCESS macro was used to evaluate the mediation of risk perception between handover quality and safety behavior. Results: Scores of psychiatric nurses’ safety behavior was (47.98 ± 7.45), and handover quality and risk perception could predict the variance of nurses’ safety behavior. Risk perception could partially mediate between handover quality and nurses’ safety behavior, and the value of the mediating effect was 49.17%. Conclusion: Psychiatric nurses’ safety behavior has large promotion space. Therefore, healthcare professionals should endeavor to improve the handover quality of psychiatric nurses and decrease their risk perception, thereby promote nurses’ safety behavior.